2009
DOI: 10.1271/bbb.90443
|View full text |Cite
|
Sign up to set email alerts
|

Feedback-Regulation of Strigolactone Biosynthetic Genes and Strigolactone-Regulated Genes in Arabidopsis

Abstract: Strigolactones (SLs) have recently been found to regulate shoot branching, but the functions of SLs at other stages of development and the regulation of SL-related gene expression are mostly unknown in Arabidopsis. In this study, we performed real-time reverse transcription-PCR (RT-PCR) and microarray analysis using wild-type plants and SL-deficient/insensitive mutants to understand the molecular mechanisms underlying SL biosynthesis and signaling. We found that there is responsiveness to SL in the gene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
164
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(186 citation statements)
references
References 29 publications
19
164
3
Order By: Relevance
“…4D). The overall mechanism for feedback regulation of SL biosynthesis is evidently conserved in diverse species (Foo et al, 2005;Snowden et al, 2005;Arite et al, 2007;Mashiguchi et al, 2009;Minakuchi et al, 2010).…”
Section: Conserved Function and Regulation Of Zmccd8mentioning
confidence: 99%
“…4D). The overall mechanism for feedback regulation of SL biosynthesis is evidently conserved in diverse species (Foo et al, 2005;Snowden et al, 2005;Arite et al, 2007;Mashiguchi et al, 2009;Minakuchi et al, 2010).…”
Section: Conserved Function and Regulation Of Zmccd8mentioning
confidence: 99%
“…Mashiguchi and co-workers found that light-signaling-related genes are induced in Arabidopsis seedlings shortly (90 min) following exposure to GR24. 48 Analysis of roots and shoots of WT tomato plants and of the SLs-deficient tomato mutant Sl-ORT1 49,50 suggested that SLs are positive regulators of plant light harvesting. This was deduced from the list of genes induced by GR24, following 24 to 48 h of GR24 treatment, which was enriched in genes putatively associated with light harvesting.…”
Section: Strigolactones Affect Shoot Developmentmentioning
confidence: 99%
“…In Arabidopsis, one transcription factor, BRANCHED1 (BRC1), has been linked to the strigolactone pathway. BRC1 is down-regulated in max mutants buds and upregulated in response to application of strigolactone (Aguilar-Martínez et al, 2007;Mashiguchi et al, 2009). As with the genes in the upstream part of the pathway, the challenge lies in identification of the functions of all these genes.…”
Section: Discovering Genes In the Pathwaymentioning
confidence: 99%